Recalibrating EU Foreign Policy Vis-à-vis Central Asia: Towards Principled Pragmatism and Resilience. Issue 3 (27th May 2023) - Winn, Neil; Gänzle, Stefan
ABSTRACT: With China and Russia acting more assertively vis-à-vis Central Asia, Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan have gradually moved to the core of contemporary Eurasian geopolitics – albeit to varying degrees. The European Union (EU) has purposefully sought to promote its norms and values in the region for quite some time in the past. However, considering the ongoing Western "polycrisis" exacerbated by the Covid-19 pandemic most recently, our paper investigates how the EU has been recalibrating its relationship towards Central Asia – within the timespan of its two EU Central Asia Strategies, dating from 2007 and 2019, respectively. We argue that the reformulation of EU policy towards Central Asia is pragmatically taking its lead from the growing constraints of EU foreign policy as well as Chinese and Russian intervention in the region; it is, in the end, geographical proximity that continues to shape geopolitics in Central Asia.